Industry 4.0: German Experience of Development of Digital Transport and Logistics - A. O. Merenkov (Управление)
Innovations are becoming more widespread in transport, determining the level of quality of passenger service. This thesis predetermined the urgency of the article, as well as the vector of research. In the article the author considers the digitalization of the transport complex through the industry paradigm 4.0, which affects various spheres of business and society. The paper presents the main characteristics of the sphere of freight forwarding services in the digital age. The article highlights the main centers of information development in transport among foreign countries, in the series of which the experience of Germany is highlighted. This state is considered to be the leaders of the European continent both in the sphere of innovations in industrial production and in the sphere of transport. For the Russian Federation, the experience of Germany in the field of introducing intelligent transport technologies is of interest. The author of the research reveals their main directions and principles, gives examples of automation in transport and logistics, reflected in the activities of companies in the real sector of the German economy. The main directions of digitalization are identified: infrastructure, autopilotation, robotization, automation of control systems. Particular attention is paid to the development of intelligent transport systems, the elements of which are autopilot. In the conclusion of the work the author formulated the conclusions that can form the basis for applying the experience of Germany in Russia.